Lafoeina longitheca Jaderholm 1904 ... - Galea, Horia R. (Zenodo, 2007)
Lafoeina longitheca Jäderholm, 1904 (fig. 8O, P, table 5) Lafoeina longitheca Jäderholm, 1904b: 4; 1905: 20, figs 1–2, pl. 8; Billard, 1914: 12; Stepanjants, 1979: 41, pl. 7 fig. 9; Blanco et al. , 2000a: 269, fig. 2; Peña Cantero et al. , 2004: 2274, fig. 1A–B. Material examined . Stn. CFA — 14.iii.2006, 10– 30 m, S88: a sterile colony, epizoic on Bougainvillia pyramidata (MHNG INVE 53322). Type locality . Off South Georgia, West Antarctica. Description . Colony minute, stolonal, with individual hydrothecae and nematothecae arising directly from a branching, anastomosing hydrorhiza, firmly attached to its substrate, a colony of Bougainvillia pyramidata . Hydrothecae long, tubular, slightly curving, generally with 2–3 widely-spaced renovations; basal part narrowing fairly suddenly and attached directly to stolon; hydrothecal pedicel absent; hydrothecal rim slightly everted. Closing apparatus composed of several triangular flaps, connected by a hyaline membrane and folding together to form a pointed roof; ... : Published as part of Galea, Horia R., 2007, Hydroids and hydromedusae (Cnidaria: Hydrozoa) from the fjords region of southern Chile, pp. 1-116 in Zootaxa 1597 (1) on page 38, DOI: 10.11646/zootaxa.1650.1.4, http://zenodo.org/record/5097970 ...